Different Functional Network Connectivity Patterns in Epilepsy: A Rest-State fMRI Study on Mesial Temporal Lobe Epilepsy and Benign Epilepsy With Centrotemporal Spike - Fu, Cong; Aisikaer, Aikedan; Chen, Zhijuan; Yu, Qing; Yin, Jianzhong; Yang, Weidong (Frontiers in Neurology, 2021)
The stark discrepancy in the prognosis of epilepsy is closely related to brain damage features and underlying 16 mechanisms, which have not yet been unraveled. In this study, differences in the epileptic brain functional 17 connectivity states were explored through a network-based connectivity analysis between intractable mesial 18 temporal lobe epilepsy (MTLE) patients and benign epilepsy with centrotemporal spikes (BECT). Resting state 19 fMRI imaging data were collected for 14 MTLE patients, 12 BECT patients and 16 healthy controls (HCs). 20 Independent component analysis (ICA) was performed to identify the cortical functional networks. Subcortical 21 nuclei of interest were extracted from the Harvard-Oxford probability atlas. Network-based statistics were used to 22 detect functional connectivity (FC) alterations across intranetworks and internetworks, including the connectivity 23 between cortical networks and subcortical nuclei. Compared with HCs, MTLE patients showed significant lower 24 activity between the connectivity of cortical networks and subcortical nuclei (especially hippocampus) and lower 25 internetwork FC involving the lateral temporal lobe; BECT patients showed normal cortical-subcortical FC with 26 hyperconnectivity between cortical networks. Together, cortical-subcortical hypoconnectivity in MTLE suggested a 27 low efficiency and collaborative network pattern, and this might be relevant to the final decompensatory state and 28 the intractable prognosis. Conversely, cortical-subcortical region with normal connectivity remained well in global 29 cooperativity, and compensatory internetwork hyperconnectivity caused by widespread cortical abnormal discharge, 30 which might account for the self-limited clinical outcome in BECT. Based on the fMRI functional network study, 31 different brain network patterns might provide a better explanation of mechanisms in different types of epilepsy.